Lymph Node Metastasis for pN+ Superficial Esophageal Squamous Cell Carcinoma - Yafan Yang; Liyan Xue; Xiankai Chen; Mingqiang Kang; Renquan Zhang; Hui Tian; Jianqun Ma; Maoyong Fu; Jinchang Wei; Qi Liu; Anlin Hao; Yi He; et al. (Thoracic Cancer)
ABSTRACT Objectives This study aimed to analyze lymph node metastasis (LNM) distribution in superficial esophageal squamous cell carcinoma (ESCC) and its impact factors on survival. Methods We reviewed 241 pT1N+ ESCC cases between February 2012 and April 2022 from 10 Chinese hospitals with a high volume of esophageal cancer (EC). We analyzed clinicopathological data to identify overall survival (OS) risk factors and LNM distribution in relation to tumor invasion depth. Results Of the 241 patients, 26 (10.8%) had pT1a cancer and 215 (89.2%) had pT1b cancer. We showed that N3 stage, ≤ 28 lymphadenectomies, and nerve infiltration (NI) were negative factors for OS in superficial pN+ ESCC, whereas the OS was not definitively affected by the tumor depth and the choice of adjuvant therapy. In general, the LNM rates of the 193 pT1N+ ESCC cases can be ranked in the following order: station 106recR > station 106recL > station 1 > station 7 > station 2. With deeper tumor invasion, the higher LNM rate was observed near the bilateral recurrent laryngeal nerves (RLN), but there was no statistically significant difference. Conclusions In superficial ESCC, LNM was frequently observed along the 106recR (35.8%) and 106recL (25.6%) stations. Advanced N‐staging (N3) was a major negative impact factor in prognosis, and adequate lymph nodes dissected (LND) (N > 28) improved OS of pT1N+ ESCC. However, in superficial ESCC, tumor infiltration depth did not affect patients' OS or the distribution of positive LNs. The optimal adjuvant treatment that favors survival for these patients required further investigation.